An effective method to suppress high-order modes of SIW filters with compact size. (September 2022) - Fan, Chenhui; Liu, Xiaoxian; Liu, Nuo; Yang, Yintang; Zhu, Zhangming
Abstract: In this paper, an effective method for substrate integrated waveguide (SIW) filter with improved stop band performance is proposed. By configuring the position and the direction of the coupling window, the transmission of the parasitic mode such as TE102 and TE201 can be effectively suppressed without adding any extra structure and element. Under the above theory, a Ka-band SIW filter centered at 35.71 GHz based on quartz glass substrate with compact size and simple structure is designed and tested. The stop rejection of the design is increased from 1.03 times to 1.95 times the center frequency within −35 dB of the filter with the insertion loss of −2.5 dB and the return loss of −20 dB. Finally, the measurement results validated the proposed design.